How and why does corporate reputation moderate mass media news' impact on market value? - Ivan A. Guitart; Manfred Schwaiger; Johanna Eberhardt (Schmalenbach Journal of Business Research (SBUR), 2024)
In this study, we investigate whether corporate reputation reduces or amplifies mass media news' impact on market value. We conceptualize reputation as comprising a prior knowledge, prominence, and favorability component. Additionally, we theorize about its role in moderating news' effect on market value. Using 11 semesters' data from 38 publicly listed German companies, we offer evidence of corporate reputation amplifying both negative and positive mass media news' impact on market value. We further find that positive media mentions could reduce negative mentions' negative impact up to the point that it loses its significance. Finally, our empirical analysis suggests that reputation's moderating effect is mostly due to the favorability mechanism. Our results contribute to the literature by empirically assessing the role that reputation's multiple dimensions play in shaping investors' response to positive and negative mass media news. Our results also show that ensuring the media's positive coverage of the company is an effective strategy to mitigate bursts of negative news' negative consequences.
Keywords: 650; Corporate reputation; Market value; Mass media news; News valence